Pengalaman Komunikasi Personel Badan Penghubung Sumatera Barat Dengan Perantau - Stefan Antonio; Emeraldy Chatra; Asmawi Asmawi (Mahesa Research Center, 2021)
The West Sumatra Liaison Agency is one of the government organizations of West Sumatra Province. This organization is located outside West Sumatra, especially in Jakarta. The West Sumatra Liaison Agency functions to facilitate the West Sumatra Provincial Government and the Central Government. This study aims to explore the experience of the Liaison Agency personnel in the perspective of symbolic interaction theory. Research with qualitative methods using a phenomenological approach is more focused on exploring the stages of interpersonal communication in communicating with migrants from West Sumatra from the perspective of symbolic interaction theory. The informants of this study consisted of 6 people, of which three people served in the West Sumatra Liaison Agency and three people who were staff. The research informants were selected by purposive sampling technique. The results of this study indicate that personnel who are organizational officials have different concepts of thought, self-concept, and interaction / community concepts from personnel who are staff at the West Sumatra Liaison Agency.